Differences between successful and unsuccessful Euroleage teams based on nonstandard efficiency parameters - Perica, A.; Jelaska, I.; Trninic, S. (Acta Kinesiologica, 2014)
This research was conducted to investigate and explain the differences between successful and unsuccessful basketball teams in the 2009/2010 championship season of the Euroleague Top 16. Certain nonstandard situational variables in positional offence and defence are defined to explore the structure of the game in detail. The resulting discriminant function significantly differentiates successful from unsuccessful teams (p<0.01). The results indicate that the components of positional defence that most determine its success are successful individual defence of the ball on the perimeter (including proper close-outs) and successful team penetration defence. On the other hand, unsuccessful positional defence is mostly determined by unsuccessful team penetration defence, unsuccessful defence against inside cutting, and unsuccessful individual and team defence on the low-post. For successful positional offence, the most important factors we found were pick and roll/pop and handoff manoeuvres, while unsuccessful ball penetrations from the perimeter, unsuccessful pick and roll/pop and handoff manoeuvres and unsuccessful perimeter isolations characterise an unsuccessful positional offence. The results indicate the main focal points for technical and tactical preparation of professional players and teams.